Drug-Induced Liver Injury during Antidepressant Treatment: Results of AMSP, a Drug Surveillance Program. (30th December 2015) - Friedrich, Michaela-Elena; Akimova, Elena; Huf, Wolfgang; Konstantinidis, Anastasios; Papageorgiou, Konstantinos; Winkler, Dietmar; Toto, Sermin; Greil, Waldemar; Grohmann, Renate; Kasper, Siegfried
Abstract : Background: Drug-induced liver injury is a common cause of liver damage and the most frequent reason for withdrawal of a drug in the United States. The symptoms of drug-induced liver damage are extremely diverse, with some patients remaining asymptomatic. Methods: This observational study is based on data of Arzneimittelsicherheit in der Psychiatrie, a multicenter drug surveillance program in German-speaking countries (Austria, Germany, and Switzerland) recording severe drug reactions in psychiatric inpatients. Of 184234 psychiatric inpatients treated with antidepressants between 1993 and 2011 in 80 psychiatric hospitals, 149 cases of drug-induced liver injury (0.08%) were reported. Results: The study revealed that incidence rates of drug-induced liver injury were highest during treatment with mianserine (0.36%), agomelatine (0.33%), and clomipramine (0.23%). The lowest probability of drug-induced liver injury occurred during treatment with selective serotonin reuptake inhibitors ([0.03%), especially escitalopram [0.01%], citalopram [0.02%], and fluoxetine [0.02%]). The most common clinical symptoms were nausea, fatigue, loss of appetite, and abdominal pain. In contrast to previous findings, the dosage at the timepoint when DILI occurred was higher in 7 of 9 substances than the median overall dosage. Regarding liver enzymes, duloxetine and clomipramine were associated with increased glutamat-pyruvat-transaminase and glutamat-oxalat-transaminase values, while mirtazapine hardly increased enzyme values. By contrast, duloxetine performed best in terms of gamma-glutamyl-transferase values, and trimipramine, clomipramine, and venlafaxine performed worst. Conclusions: Our findings suggest that selective serotonin reuptake inhibitors are less likely than the other antidepressants, examined in this study, to precipitate drug-induced liver injury, especially in patients with preknown liver dysfunction.